Short Film Media: Creating Student Learning Convenience - Tabroni, Imam (Trigin Institute, 2023)
Audio-visual media is media that has sound elements and picture elements. This type of media has better capabilities, because it includes both types of auditory (hearing) and visual (seeing) media. Audio visual media is an audiovisual aid which means materials or tools used in learning situations to assist written and spoken words in conveying knowledge, attitudes, and ideas. Another definition of audio-visual media is a set of tools that can project moving images and sound. The combination of picture and sound forms the same character as the original object. This article is intended to conduct audio-visual media research on early childhood in the classroom. This research was addressed to grade 2 students of Al Ghazali Islamic Elementary School. The aim of this research was to describe how audiovisual media influences early childhood. There are a total of 30 students at the Islamic elementary school Al Ghazali Purwakarta. The data were collected through a questionnaire instrument from audio-visual media variables and also student test results as a variable on average student achievement. The results of the data are processed through statistical calculations and average correlations, obtained through the use of SPSS 16.0. The data shows the interpretation of the high level of reliability, the magnitude of the influence of audio-visual media on children’s learning comfort is 48.1%.